FACTORS ASSOCIATED WITH WHETHER OLDER ADULTS DISCUSS THEIR EOL CARE PREFERENCES WITH FAMILY MEMBERS. (11th November 2018) - Peterson, L J; Hyer, K; Meng, H; Dobbs, D; Gamaldo, A; O'Neil, K
Abstract: Research suggests end-of-life (EOL) care discussions improve EOL care. This study examined factors associated with having discussed EOL care wishes with family, focusing on race and ethnicity. A diverse sample of participants (N=364) completed surveys including questions about demographics, discussing one's EOL care preferences, family involvement in general health care, and communication with doctors. Results showed more than 30% had not discussed their EOL care wishes with family. There were no differences by race, but there were significant differences by ethnicity. Hispanic participants were less likely (O.R.= 0.40, p=.03), however moderation analysis showed Hispanics with greater family involvement in general health care were much more likely to have discussed EOL preferences with family (O.R.= 5.69; p=.02). Lesser confidence in communicating with doctors was associated with lower likelihood of discussion with family (O.R.= 0.65, p=.03). Results suggest providers consider ethnicity and family involvement in efforts to encourage EOL care discussions.